TINJAUAN UNDANG-UNDANG NOMOR 30 TAHUN 2004 TENTANG JABATAN NOTARIS TERHADAP PERANAN NOTARIS DALAM PEMBAGIAN HARTA WARISAN SECARA TESTAMENTER - Rodiansyah Rodiansyah (Journal of Law ( Jurnal Ilmu Hukum ), 2014)
ABSTRACTSomeone to be able to inherit under the law of inheritance west known presence of 2 ways inherited based on the Act (Ab Intestato) and inherit based on a will (Ad Testamato). Testamentary inheritance problems with deed (acte testament) has been around a long time, on the last will or testament deed (acte testament) in general is a statement from someone before she died and carried out after death. Creating a testament deed (acte testament) is a legal act, of a person who acts against the legacy assets after he died, so in making a will is a legal act unilaterally in this case very closely connected with nature "herroepelijikheid" (can be revoked ) from the provisions of a will (testament) is.In making a will (testament) there is some kind of a will (testament) based on its shape, namely, among others: Miraculous olographis, general or openbaar testament Probate, Wills closed or secret, but it is also contained a will (testament) codicil. In doing actions to fulfill the will of the testator, Notaries can only act as a fair referee and should not take sides in terms of difficulty and hesitation of the heir.